ФОРМУВАННЯ В УЧНІВ ОСНОВНОЇ ШКОЛИ КРАЄЗНАВЧИХ ЗНАНЬ У ПРОЦЕСІ ВИВЧЕННЯ ГЕОГРАФІЧНИХ КУРСІВ (Педагогіка вищої та середньої школи, 2010)
The selectin and heterolevels aim formation criteria, forms, in the process of secondary school's local lor, history, and economy work has been worked out have been theoretically defined.